IBX-Mediated Organic Transformations in Heterocyclic Chemistry-A Decade Update - Venkata Durga Nageswar, Yadavalli; Ramesh, Katla; Rakhi, Katla (Frontiers in Chemistry, 2022)
O-Iodoxybenzoic acid (IBX) is a very mild and efficient hypervalent iodine synthetic reagent useful to carry out several selective oxidations. The present review highlights research reports on IBX-assisted transformations in heterocyclic derivatives, particularly from 2010 onward.